Tannase Activity Optimization and Antibiotic Resistance Profiling of Bacteria Isolated from Goat Feces and Ruminal Fluid - Mohd Zaki, Nur Farah Syuhada; Aris, Farizan; Mohamed Yunus, Norfatimah; Mat Jalil, Mohd Taufiq; Zakaria, Nurul Aili (HAYATI Journal of Biosciences, 2025)
Tannase is a vital enzyme produced by microorganisms in the rumen and gastrointestinal tracts of animals, capable of converting tannins—a common anti-nutritional factor in feeds. This study optimized physicochemical conditions of pH, temperature, substrate concentration, and incubation time for evaluating crude tannase activity in tannin-degrading bacteria (TDB) isolated from ruminal fluid (TDB17: Lysinibacillus macroides (KR780381), TDB18: Acinetobacter nosocomialis [MH084921], TDB23: Acinetobacter nosocomialis [MT540255]), and goat feces (TDB24: Acinetobacter nosocomialis [MT540255]). Among these, TDB23: A. nosocomialis (MT540255) demonstrated the highest tannase activity, reaching 96.83 U/ml under optimized conditions. Interestingly, TDB17: L. macroides (KR780381) and TDB24: A. nosocomialis (MT540255) exhibited thermostable tannase across a temperature between 20°C and 80°C, with sustained activity in the range of 60.15-50.34 U/ml and 29.93-28.98 U/ml, respectively. Additionally, the antibiotic resistance profile of these TDB and the synergistic effects of its crude tannase were evaluated using a disc diffusion assay. All TDBs were susceptible to meropenem, tigecycline, gentamicin, streptomycin, and chloramphenicol but resistant to penicillin G, cephalothin, cefoxitin, and vancomycin. Notably, A. nosocomialis (TDB18, TDB23, and TDB24) demonstrated sensitivity to sulfamethoxazole, while L. macroides (TDB17) exhibited resistance. Moreover, the crude tannase synergistically enhanced the antibacterial activity of antibiotics (p<0.05) against both Gram-positive and Gram-negative bacteria.